Investigating English-Indonesian Translation of Intransitive Phrasal Verbs in Brown’s Principle of Language Learning and Teaching - Dedy Yulianto; Widhiya Ninsiana; Ahmad Subhan Roza (Jurnal Pedagogy, 2019)
This research concerned with the translation of intransitive phrasal verb in Brown’s Principle of Language Learning and Teaching from English into Indonesian. The type of this research was qualitative research which dealt with non-numerical data. This research was analyzed by using the techniques proposed by Cresswell. There are six steps, namely (1) preparing the data for analysis; (2) looking and reading all the data; (3) coding all the data; (4) using the coding to describe the setting; (5) making advanced description; and (6) making interpretation. The finding results show that the accuracy level and readability level in Brown’s Principle of Language Learning and Teaching from English into Indonesian are fair with average score 2.2. The total of intransitive phrasal verbs is 17 with details: 2 sentences of accurate translation (12%); 1 sentence of inaccurate translation (6%); 14 sentences of less accurate (82%) while the readability level shows that there is 0 of readable translation; 15 less readable sentences (88%); 2 sentences not readable translation (12%).